Atomic‐Sized Pores Enhanced Electrocatalysis of TaS2 Nanosheets for Hydrogen Evolution. Issue 40 (25th August 2016) - Li, Hui; Tan, Yongwen; Liu, Pan; Guo, Chenguang; Luo, Min; Han, Jiuhui; Lin, Tianquan; Huang, Fuqiang; Chen, Mingwei
Abstract : A plasma oxidation method is developed to fabricate atomic‐scale pores in the basal planes of electrochemically inert TaS2 nanosheets to functionalize the 2D crystals with high electrocatalysis for hydrogen evolution reaction. Quantitative measurements of under‐coordinated atoms at edges of the pores by aberration‐corrected transmission electron microscopy reveal the intrinsic correlation between the defective atomic sites and electrocatalytic activities of 2D TaS2 .